Implementing the SKUA Program (Ubudiyah and Akhlakul Karimah Proficiency Standards) in Developing Students’ Religious Competence in Madrasah Ibtidaiyah - Fanani, Zaenal; Ma'arif, Muhammad Anas (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The implementation of the SKUA Program (Ubidiyah and Akhlakul Karimah Proficiency Standards) at MI Nurul Huda 1 Miji, Kranggan District, Mojokerto City, aims to develop students' religious competencies as a whole. This program focuses on strengthening worship skills, understanding religious values, and shaping moral character as part of efforts to form a generation of noble character. This study uses a qualitative descriptive method with a case study approach. Data was collected through interviews, observations, and documentation involving madrasah heads, teachers, students, and parents. The focus of the research is the process of planning, implementing, and evaluating the program. The results of the study show that the implementation of the SKUA program is carried out through habituation of worship, integration of religious values in learning, and moral mentoring activities. Program evaluation includes direct observation and assessment of changes in student attitudes. This program has succeeded in improving students' worship skills, religious understanding, and character building. Supporting factors include teacher commitment, parental support, and a conducive environment, while the main challenges are consistency of implementation and time constraints. This program has proven to be effective in improving students' religious competence and can be used as a model for other madrasas.